Location Matters: Geographic Location and Educational Placement of Students With Developmental Disabilities. (June 2015) - Brock, Matthew E.; Schaefer, John M.
Despite decades of advocacy, most students with developmental disabilities continue to spend the majority of the school day in self-contained special education classrooms. However, there is tremendous variability of educational placement across the United States. Identification of geographic trends that explain this variability could provide opportunities for targeted advocacy. Using state-level data in Ohio, we tested the hypothesis that urbanicity predicts educational placement. Through mapping and multivariate analysis of variance, we found that students in urban districts tended to spend less time in general education classrooms, and students in rural districts tended to spend more time in general education classrooms. Furthermore, the urban districts with the largest enrollments tended to place an even lower proportion of students in general education classrooms. Given their disproportionate influence on state trends and propensity toward more self-contained and segregated placements, large urban districts offer a unique opportunity for targeted advocacy and change.